Transition from a renal paediatric clinic to an adult clinic: Perspectives of adolescents and young adults, parents and health professionals. (December 2022) - Crawford, Kimberley; Low, Jac Kee; Le Page, Amelia K; Mulley, William; Masterson, Rosemary; Kausman, Joshua; Cook, Natasha; Mount, Peter; Manias, Elizabeth
The management of chronic kidney disease is complex. With disease management being the responsibility of parents in the paediatric renal clinic, the responsibility is gradually shifted to adolescents and young adults during the transition to adult care. This multi-perspective qualitative study aimed to explore the experiences of adolescents and young adults, their parents and health professionals to gain an insight into transitional care. Focussing on the transition process and transfer to adult care, 18 adolescents and young adults and eight mothers participated in individual semi-structured interviews. Additionally, three focus groups were conducted with 20 multidisciplinary health professionals. Data were transcribed verbatim and analysed thematically. Similar responses from adolescents and young adults and mothers included the reluctance to leave the paediatric health service. Mothers found the transition to adult care more challenging than the adolescents and young adults. While health professionals acknowledged that engaging adolescents and young adults in their own care was challenging, they believed parents had an important role in facilitating their child's independence. This study highlights that health professionals in both paediatric and adult health services need to work collaboratively. However, importantly, health professionals need to be mindful that parents require an equal amount of engagement as adolescents and young adults, if not more, to mitigate parental barriers in achieving a successful transfer.